Privacy-preserving co-synthesis against sensor–actuator eavesdropping intruder. (April 2023) - Tai, Ruochen; Lin, Liyong; Zhu, Yuting; Su, Rong
Abstract: In this work, we investigate the problem of privacy-preserving supervisory control against an external passive intruder via co-synthesis of a dynamic mask, an edit function, and a supervisor. We attempt to achieve the following goals: (1) the system secret cannot be inferred by the intruder, i.e., opacity of secrets against the intruder, and the existence of the dynamic mask and the edit function should not be discovered by the intruder, i.e., covertness of dynamic mask and edit function against the intruder; (2) some safety and nonblockingness requirement should be satisfied. We assume the intruder can eavesdrop both the sensing information generated by the sensors and the control commands issued to the actuators. Our approach is to model the co-synthesis problem as a distributed supervisor synthesis problem in the Ramadge–Wonham supervisory control framework, and we propose an incremental synthesis heuristic to incrementally synthesize a dynamic mask, an edit function and a supervisor. The effectiveness of our approach is illustrated on an example about location privacy.